Effectiveness of an Online Course in Programming in a State University in the Philippines - Dela Rosa, Aaron Paul M. (International Journal of Computing Sciences Research, 2023)
Purpose – Online courses, as a pedagogical approach to teaching, boomed during this Coronavirus Disease 2019 (COVID-19) pandemic era. Universities shifted from traditional face-to-face classes to online distance learning due to the cause of the pandemic. This study aimed to determine how effective an online course is in learning a programming course. Method – The study utilized mixed-method research applied through a validated survey questionnaire consisting of closed- and open-ended questions. Python programming was the course selected to undergo the study and underwent an evaluation to determine the students’ responses. Student respondents are from Bulacan State University, a state university in the Philippines, under the Bachelor of Science in Information Technology program. Results – Based on their responses, the students found that the online Python programming was Very Effective, with an overall mean of x̄=4.49. This result shows that students found the online course effective, provided the proper course design and content, allowed them to spend enough time finishing tasks, and provided communication and interaction with their instructor and fellow students. Additionally, students gave overwhelmingly positive responses when asked what their instructors had done well on the course delivery and provided insightful and constructive comments for further enhancement and delivery of the course. Conclusion – This study found that most students strongly agreed and believed in the effectiveness of delivering the Python Programming course asynchronously. With such positive results from the student’s perspective and evaluation, the course can be enhanced to continue providing quality education at Bulacan State University. Recommendations – Revisit the course syllabus to identify the contents that should be well interconnected. Include more examples, exercises, quizzes, and activities throughout the course to help students assess their learning. Provide more means of communication and interaction with students even if the course is delivered asynchronously. Research implications – Considering its results, this study shows that programming courses delivered in higher education institutions could be delivered successfully through online learning, with asynchronous learning modality, and that faculty members can still intervene with students’ learning to address questions and clarifications.